Retail product management : buying and merchandising - Varley, Rosemary (New York : Routledge, 2006)
This text represents a specialist text resource for students of retail management or marketing courses and modules, providing the reader with the opportunity to acquire a deeper knowledge of a key area of retailing management
1. Introduction to Retail Product Management : Scope and Concepts -- 2. The Role of Retail Product Managers -- 3. Category Management -- 4. Product Range Planning and Selection -- 5. Supply Sources -- 6. Ordering Quantities and Stock Control -- 7. Managing the Response to Sales -- 8. Allocating Space to Products -- 9. Retail Design -- 10. Visual Merchandising -- 11. Communicating the Product Offer -- 12. Evaluating Retail Product Management Performance -- 13. Product Management in Non-Store Retailing -- 14. International Retail Product Management
Includes index.
Keywords: RETAIL TRADE